Investigation of the applicability of cellular thermal shift assay (CETSA) for monitoring HMG-COA reductase levels in HCT-116 - Almario, Trystam Eymar R.​; Velasquez, Dethalee Gabrielle R.​
Poor success rates of drug development process may be due to lack of determination of target engagement on a more suitable assay system. CETSA is a novel technique which monitors target engagement in unmodified proteins through the measurement of thermal shift of target protein with ligand when exposed to a range of temperature. However. CETSA has no established protocols yet for screening crude extracts. With the rising popularity of organic products, researchers are driven to provide scientific explanation behind observable effects of crude extract preparations.